Implementation of Anti-Corruption Values Through Extracurricular Activities in Elementary School: Literature Reviews - Kusumaning Ayu, Rr. Fadila; Nafiah, Nafiah; Rahayu, Dewi Widiana; Akhwani, Akhwani (Universitas Nahdatul Ulama Surabaya, 2022)
Abstract: This study aims to systematically review articles on the implementation of anti-corruption values ​​through extracurricular activities in elementary schools from 2018-to 2022. The method of this study is qualitative research, the type of this study is a systematic review based on a review of the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) flow. PRISMA can help researchers to evaluate the results of keyword experiments based on the results of randomized reviews. The data collected in this study relates to the implementation of anti-corruption values ​​through extracurricular activities in elementary schools, supporting factors, and inhibiting factors. The data collection technique used in this study uses identification, screening, eligibility, and included techniques. The data analysis in this study is related to (a) the parties involved in the implementation of anti-corruption values ​​are elementary school students, (b) activities for the application of anti-corruption values, namely extracurricular activities, (c) methods in implementing anti-corruption values ​​through extracurricular activities. in elementary schools, (d) obstacles and supporters in the implementation of anti-corruption values ​​through extracurricular activities in elementary schools, (e) evaluation results of the implementation of anti-corruption values ​​through extracurricular activities in elementary schools. As for the results of the research, the majority of relevant articles were found using a qualitative methodology, the parties involved were the principal, extracurricular teachers, and students. Extracurriculars that are often used in research are Scouts, Pencak Silat, Youth Red Cross (PMR). The supporting factor for success is the existence of self-awareness in each individual. The inhibiting factor is the lack of knowledge possessed by teachers regarding the implementation of anti-corruption education values. In the activities of implementing anti-corruption values ​​through extracurricular activities in elementary schools, some values grow in each student to affect student learning outcomes.